Implementation Of E-Performance In Improving Employee Work Productivity at The Regional Inspectorate Office Of Palopo City - Anisah; Herman H; Muhammad Darwis (International Journal Of Public Policy and Bureaucracy, 2026)
This study aims to examine how the implementation of E-performance in Improving Employee Work Productivity at the Palopo City Regional Inspectorate Office. This type of research is qualitative using a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis techniques used consisted of data collection, data display, data condensation, and drawing conclusions. The results of the study indicate that the Implementation of E-performance in Improving Employee Work Productivity at the Palopo City Regional Inspectorate Office has been running well based on three Franklin & Ripley indicators, namely the level of compliance, smooth routines, and impacts (benefits). In the compliance indicator, employees showed a fairly good awareness in fulfilling the obligation to input work activities. From the aspect of smooth routines, the e-Performance implementation process also ran quite stably. The workflow—starting from inputting activities, carrying out tasks, to superior approval—can be implemented thanks to effective coordination between departments. In the impact (benefit) indicator, e-Performance has been proven to provide a positive contribution to improving employee and agency performance. This system facilitates structured activity recording, expedites the reporting process, and increases transparency and fairness in assessments because all data is recorded objectively. Furthermore, its implementation encourages the development of employees' digital skills. The challenges that arose were primarily technical in nature and did not impact the overall quality of implementation.